Energy storage systems and their sizing techniques in power system - A review - Jamali, A.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
The increasing penetration of renewable energy sources in electrical grids mandates to utilize some energy storage to overcome the variations of intermittent power outputs. The energy storage technologies can help in balancing the generation and demand by storing unused electricity and then supplying it back to grid when required. In future grids, energy storage technologies are expected to become a major source of electricity; a collaborator to those distributed generations (DG) resources. The objective of this research was to review different energy storage systems (ESS) and their sizing techniques, used in power system. Study focused on Mechanical Energy Storage (MES), Electric and Magnetic Energy Storage (EMES) and Electro-Chemical Energy Storage (ECES) systems. Through this review, it is known that most of the research regarding energy storage sizing for large PV plants follow similar techniques as used for standalone PV systems. Additionally some authors have proposed energy models which considered only daily or yearly energy demand without considering certain network constraints. Estimating energy storage capacity without considering the electrical networks constraints may pose a threat to future energy balance predictions leading to a huge loss of investment due to unplanned storage sizing. Therefore it is recommended that current energy models used for sizing of energy storage should be reconsidered and re-designed. Â© 2015 IEEE.